Education Budget Efficiency: Challenges and Solutions in the Modern Era at SD IT Al-Fitrah - Ara Hidayat; Ana Anisa; Anisa Siti Hodijah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to explore the efficiency of education budget management at SD IT Al-Fitrah and identify challenges and solutions that can be applied in the context of modern education. The method used in this research is a qualitative approach with data collection techniques through in-depth interviews, observation and document analysis related to school budget management. The data obtained were analyzed thematically to identify relevant patterns. The results show that although SD IT Al-Fitrah has tried to manage its budget well, there are some significant challenges faced, including wasteful use of funds and lack of allocation for facility development. Around 15% of the total budget is left over each year. In addition, the utilization of information technology in budget management is still limited, which hampers operational efficiency. This study recommends the implementation of a more transparent budget planning and evaluation system, increased utilization of information technology, and better collaboration with parents and communities to support education budget efficiency.